2003
DOI: 10.1177/09500170030173002
|View full text |Cite
|
Sign up to set email alerts
|

`A Unique Working Environment': Health, Sickness and Absence Management in UK Call Centres

Abstract: This article fills an important gap in our knowledge of call centres by focusing specifically on occupational ill-health. We document the recent emergence of health and safety concerns, assess the responses of employers and the Health and Safety Executive (HSE), critique the existing regulatory framework and present a holistic diagnostic model of occupationally induced ill-health. This model is utilized to investigate quantitative and qualitative data from a case study in the privatized utility sector, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0
10

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 18 publications
5
68
0
10
Order By: Relevance
“…However, compared with other service sector workers, call center employees report even fewer opportunities to influence their jobs, which is a finding that provides support for earlier claims about the restricted task discretion and low task variety afforded to the employees in call centers (Grebner et al, 2003;Taylor et al, 2003;Zapf et al, 2003). The most notable differences are found between the comparison groups when the autonomy index is disaggregated.…”
Section: Job Resources Autonomysupporting
confidence: 61%
See 1 more Smart Citation
“…However, compared with other service sector workers, call center employees report even fewer opportunities to influence their jobs, which is a finding that provides support for earlier claims about the restricted task discretion and low task variety afforded to the employees in call centers (Grebner et al, 2003;Taylor et al, 2003;Zapf et al, 2003). The most notable differences are found between the comparison groups when the autonomy index is disaggregated.…”
Section: Job Resources Autonomysupporting
confidence: 61%
“…At the same time, a relatively large body of literature has shown that call centers are specific workplaces which incorporate work conditions that have the potential to negatively affect employee well-being. For the employees, the introduction of Taylorist forms of industrial engineering models in call center environments has meant the experiencing of a degradation in working conditions, the routinization of work processes, boredom, and increased stress, which are associated with the speeding up of job cycle times (Knights and McCabe, 1998;Taylor and Bain, 1999;Taylor et al, 2003).…”
mentioning
confidence: 99%
“…The biggest single occupational grouping in our sample is call-centre workers, recruited with the help of key research contacts and then through snowball sampling. This work location fits neatly with the burgeoning literature (see, for example, Bain et al, 2002;Belt et al, 2002;Deery et al, 2002;Taylor et al, 2002Taylor et al, , 2003 on an employment sector that is profoundly emblematic of Britain's service economy. Working in a sector that is overwhelmingly non-unionized, most of our call centre contacts were paid just over minimum wage, struggled with unsociable shift patterns, and suffered the indignities of incredibly intrusive micromanagement (see Winlow and Hall, 2006, for a more detailed account).…”
supporting
confidence: 67%
“…Leur zone d'autonomie serait alors restreinte et leur engagement plutôt instrumental. Le stress, engendré par cette pression, peut mener à certaines conséquences négatives pour l'organisation, telles que la fatigue émotionnelle des employés (Deery, Iverson et Walsh, 2002), l'augmentation du taux d'absentéisme pour cause de maladie (Taylor et al, 2003), l'émergence de diverses formes de résistance (Barnes, 2007) ou leur démission (Schalk et Van Rijckevorsel, 2007).…”
Section: Angles Analytiques Des éTudes Portant Sur Les Centres D'appelsunclassified